The Intersections of Race, Gender, and Religion in Leila Aboulela's Minaret - Leilya Putri Ramadhani; Siti Hanifa (Program Studi Bahasa Inggris Universitas Trunodjoyo Madura, 2026)
Abstract: The intersection of race, gender, and religion creates complex and often invisible forms of marginalization for women of color in Western societies, especially Muslim women who face overlapping systems of discrimination that cannot be understood through single-axis frameworks. This study aims to examine how these intersecting identities shape both marginalization and agency in Leila Aboulela’s Minaret (2005), with a focus on the protagonist Najwa’s transformation from a privileged Sudanese university student to a marginalized domestic worker in London. Using a qualitative descriptive approach rooted in naturalistic inquiry, the study employs close reading techniques to analyze character dialogues, narrations, and internal monologues, utilizing the qualitative method of Miles et al. (2014) three-step analytical process of data condensation, data display, and conclusion drawing. The analysis shows that Najwa’s identity as a Sudanese Muslim woman is deeply influenced by systemic intersections of racial hierarchies, gender roles, and religious marginalization that create unique forms of discrimination beyond individual identities. The findings show how her privilege in Sudan loses meaning within London’s racialized labor markets, pushing her into exploitative domestic work that reflects Collins’ “Mammy” controlling image while also limiting her agency through structural barriers. Despite systemic restrictions, Najwa shows limited agency through religious practices and subtle acts of resistance, though these are heavily constrained by intersecting systems that use her multiple identities to justify exploitation while erasing her complexity and humanity.